The Impact of Hybrid Learning Assisted Google Site and QR-Code Model on Understanding Concept Ability of Multiplication in Elementary School Students - Martiasari, Asih; Ristiana, Muhammad Ghiyats (PrimaryEdu : Journal of Primary Education, 2023)
Understanding mathematical concepts in multiplication material are indispensable for solving mathematical problems as well as a prerequisite for the next higher material. Based on several studies the lack of students understanding the multiplication concepts is due to internal factors such as the lack of student motivation and external factors such as the lack of innovative learning media used by teachers. Therefore, the approach using ICT (Information and Collaboration Technologies) is expected to be impactful and the development of today's education. This study aims to see the impact of hybrid learning assisted by Google Site and QR Code model on understanding the concept ability of multiplication. This study used quantitative methods with one group pretest-posttest design. The population in this study were 3rd-grade elementary school students with a sampling technique using purposive sampling of as many as 34 students. From this research, it is known that the use of hybrid learning assisted by Google Site and QR Code model impacts understanding concept ability of multiplication which is characterized by an increase in the achievement of results by 0.5 or with moderate interpretation, as well as students' understanding of the multiplication concept and the causes of students' difficulties in understanding the multiplication concept. Based on the results of the study, it can be concluded that the impact of using a hybrid learning assisted by Google Site and QR Code model is an increasing understanding concept ability of multiplication. In the use of hybrid learning assisted by Google Sites and QR Code model, students found difficulties in understanding the concept ability of multiplication. This is shown by students not being able to distinguish multiplier numbers and multiplied numbers, difficulty in interpreting the language of the problem, and still lacking numeracy literacy.